Analysis of Factors Affecting Regional Development in Iran - hujjat mirzazadeh; Taher Parizadi (تحقیقات کاربردی علوم جغرافیایی)
Introduction and Objectives: Unbalanced distribution facilities and services on Economic, Social and between regions, need to the planning and balanced spatial development the spatial structure of the country is inevitable This study aimed to determine the level development of the provinces of Iran and rank them based on the level of development and different levels of development of the country From 1345 to the present to help make the planning system and national policy has been done.